2016
DOI: 10.1002/jbmr.2991
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Abaloparatide-SC on Fractures and Bone Mineral Density in Subgroups of Postmenopausal Women With Osteoporosis and Varying Baseline Risk Factors

Abstract: Abaloparatide-SC is a novel 34-amino acid peptide created to be a potent and selective activator of the parathyroid hormone receptor type 1 (PTHR1) signaling pathway. In the Abaloparatide Comparator Trial in Vertebral Endpoints (ACTIVE) Phase 3 trial (NCT01343004), abaloparatide reduced new morphometric vertebral fractures by 86% compared with placebo (p < 0.001) and nonvertebral fractures by 43% (p ¼ 0.049) in postmenopausal women with osteoporosis. Abaloparatide-SC increased bone mineral density (BMD) 3.4% a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 18 publications
3
69
0
6
Order By: Relevance
“…PTH(1-34) (teriparatide) reduces vertebral and nonvertebral fracture risk, in part, by increasing bone matrix volume. Abaloparatide has also recently been reported to reduce morphometric vertebral fracture risk (1,2) and is thus a most welcome addition to the therapeutics of bone fragility. Abaloparatide is claimed to produce its anabolic effect with a much lesser effect on bone resorption than occurs with teriparatide.…”
mentioning
confidence: 99%
“…PTH(1-34) (teriparatide) reduces vertebral and nonvertebral fracture risk, in part, by increasing bone matrix volume. Abaloparatide has also recently been reported to reduce morphometric vertebral fracture risk (1,2) and is thus a most welcome addition to the therapeutics of bone fragility. Abaloparatide is claimed to produce its anabolic effect with a much lesser effect on bone resorption than occurs with teriparatide.…”
mentioning
confidence: 99%
“…Within this group are the bisphosphonates, which inhibit protein prenylation in the mature osteoclast, reducing osteoclast capacity to resorb bone, (1) and denosumab, a monoclonal antibody to RANK ligand that inhibits osteoclast formation, function, and survival. (2) Although several new anabolic agents are in development, (3)(4)(5) teriparatide is currently the only available anabolic therapy for osteoporosis in the United States, with the addition of only PTH in the EU (referred to as PTH). Teriparatide (TPTD) and PTH act by direct stimulation of osteoblast activity and recruitment (both remodeling and modeling-based formation) as well as stimulation of remodeling, favoring bone formation (remodeling-based formation).…”
Section: Introductionmentioning
confidence: 99%
“…A previous prespecified analysis of risk factor subgroups in ACTIVE (defined identically as for the analysis reported here) demonstrated similar findings: the efficacy of abaloparatide for fracture risk reduction and BMD gains was consistent across a wide variety of ages and baseline risk, including those with and without prior fractures at study baseline. (3) Likewise, a prespecified analysis of subgroups defined by geographic region showed that despite geographic variability in baseline fracture risk, there were no differences by region in the effects of abaloparatide for reducing fracture risk across the regions and ethnicities assessed. (14) The limitations of this analysis are similar to those of other subgroup analyses in which statistical significance was not adjusted for multiple comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of prespecified subgroups from ACTIVE demonstrated that fracture risk reductions and increases in BMD were consistent across a wide variety of baseline risk factors, including BMD T-scores at lumbar spine, total hip, and femoral neck, age, prevalence of vertebral fracture, history of nonvertebral fracture, and baseline fracture risk as assessed by FRAX. (3,4) At the end of ACTIVE, patients from the abaloparatide and placebo groups were given the opportunity to enroll in an extension study, ACTIVExtend (NCT01657162), to receive 24 months of sequential antiresorptive treatment with alendronate. Results from the full 43 months of the integrated ACTIVE-ACTIVExtend (18 months of abaloparatide or placebo in ACTIVE, with about 1 month off treatment for re-consent, followed by 24 months of alendronate treatment) have been published.…”
Section: Introductionmentioning
confidence: 99%